Senecio tephrosioides Turcz. (Asteraceae): A review of ethnobotany, phytochemistry and pharmacology - Blanco, Cyntia Marysol; Olascuaga-Castillo, Karyn Alicia; Valdiviezo-Campos, Juan Ernesto; Rubio-Guevara, Susana Del Rocio (Ethnobotany Research and Applications, 2020)
Background: Senecio tephrosioides Turcz. (Family: Asteraceae) is a traditional medicinal plant used in various systems of ancient medicine in Peru for its ethnopharmacological value to cure varieties of ailments. Terpenes (1-isopropyl-4-methyl bicyclo [3,1,0] hexane and terpinene), phenolic compounds (5,7-dihydroxy-4 ’, 6’, 8-trimethoxyflavanonone, 3 ’, 5’-dihydroxy- 4-methoxy-7-0-rhannoglucosyl flavanonone and 5,4-dihydroxychalcone), flavonoids (quercetin-3-rutinoside), pyrrolizidine alkaloids (neoplatypillin, Senecionin, seneciphylline, seneciphylline N-oxide and senkirkine), and are the lactones main active components obtained from the aerial parts of this genus, and which are importantly related in traditional preparations for the treatment and management of diseases. This mini-review focuses mainly on the botanical aspects, ethnopharmacology, the main secondary metabolites, and the possible medicinal uses of Senecio tephrosioides. Materials and Methods: The sources for the literature search were Scielo, PubMed, ScienceDirect and Google Scholar. Results: The reported pharmacological activities, secondary metabolites, and traditional uses of Senecio tephrosioides justify its possible therapeutic uses. Conclusions: However, more studies are still required that go hand in hand with scientific validations and standardizations using orthogonal methods such as Nuclear Magnetic Resonance (NMR), High Resolution Liquid Chromatography (HPLC) and Mass Spectrometry - coupled to Liquid Chromatography (MS -LC), contrast traditional knowledge with evidence through methodological tests that allow to determine the safety and functioning of the components of this species, as well as an opportunity in the discovery and development of new drugs from purified natural products or crude extracts partitioned. Keywords: Senecio tephrosioides; Huamanripa; Huamanrripa; wamanripa; traditional uses; Medicinal plant